3D interconnected boron- and nitrogen-codoped carbon nanosheets decorated with manganese oxides for high-performance capacitive deionization. (March 2020) - Xie, Zhengzheng; Shang, Xiaohong; Yang, Jianmao; Hu, Bin; Nie, Pengfei; Jiang, Wenwen; Liu, Jianyun
Abstract: The boron- and nitrogen-codoped 3D interconnected carbon nanosheets were synthesized with chitosan hydrogel and boric acid as precursors. The obtained nanosheets were interconnected to form a 3D network with thin lamellae (thickness ∼30 nm) and abundant meso-pores. The successful doping of boron and nitrogen atoms was proved by X-ray photoelectron spectroscopy (XPS). Following the decoration of manganese oxides, the resultant B, N-codoped manganese oxide-containing 3D interconnected carbon nanosheets were highly favorable for ionic transportation and storage. The specific capacitance and desalination amount of the corresponding deionization device reached 249 F g −1 and 20.3 mg g −1, respectively. This nanosheet material exhibited a fast salt adsorption rate and high cycling stability, showing an average salt adsorption rate ( ASAR ) of 1.5 mg g −1 min −1 and the desalination retention of 90.3% after 50 cycles. B, N-dual doping introduces active sites for ion adsorption and improves the conductivity. In addition, MnO2 deposition contributes to the faradaic pseudocapacitance. This work provides a facile and novel strategy to fabricate 3D carbon nanosheets, by combination of B, N-doping and MnO2 decoration, for highly efficient deionization application. Graphical abstract: Image 1